Biological effects of dumped chemical weapons in the Baltic Sea: A multi-biomarker study using caged mussels at the Bornholm main dumping site. (October 2020) - Lastumäki, Anu; Turja, Raisa; Brenner, Matthias; Vanninen, Paula; Niemikoski, Hanna; Butrimavičienė, Laura; Stankevičiūtė, Milda; Lehtonen, Kari K.
Abstract: After World War II, thousands of tons of highly toxic chemical warfare agents (CWA) were deposited in the Baltic Sea, the main dumping site locating in the Bornholm Basin. In the present study, Baltic mussels ( Mytilus trossulus ) were transplanted in the area in cages at two hotspot sites and a reference site at the depths of 35 and 65 m for 2.5 months to study bioaccumulation and biological effects of CWA possibly leaking from the corroding warfare materials. No traces of degradation products of the measured phenylarsenic CWA could be detected in the tissues of mussels. Nevertheless, several biochemical and histochemical biomarkers, geno- and cytotoxicity indicators, and bioenergetic parameters showed significant responses. The Integrated Biomarker Index calculated from the single biomarkers also showed a higher total response at the two hotspot areas compared to the reference site. Although no direct evidence could be obtained confirming the responses being caused specifically by exposure to CWA, the field exposure experiment showed unambiguously that organisms in this sea area are confronting environmental stress affecting negatively their health and this is likely related to chemical contamination, which is possibly connected to the sea-dumped CWA. Highlights: Mussel caging was used to detect the effects of dumped chemical warfare agents. Various biomarker responses were observed in mussels in the main dumping area. Degradation products of the compounds were not detected in mussel tissues. Observed effects are potentially connected to leakage from the dumped materials.